A Human Factors Engineering Study of the Medication Delivery Process during an Anesthetic: Self-filled Syringes versus Prefilled Syringes. (April 2016) - Yang, Yushi; Rivera, Antonia Joy; Fortier, Christopher R.; Abernathy, James H.
Abstract : Background: Prefilled syringes (PFS) have been recommended by the Anesthesia Patient Safety Foundation. However, aspects in PFS systems compared with self-filled syringes (SFS) systems have never been explored. The aim of this study is to compare system vulnerabilities (SVs) in the two systems and understand the impact of PFS on medication safety and efficiency in the context of anesthesiology medication delivery in operating rooms. Methods: This study is primarily qualitative research, with a quantitative portion. A work system analysis was conducted to analyze the complicated anesthesia work system using human factors principles and identify SVs. Anesthesia providers were shadowed: (1) during general surgery cases (n = 8) exclusively using SFS and (2) during general surgery cases (n = 9) using all commercially available PFS. A proactive risk assessment focus group was followed to understand the risk of each identified SV. Results: PFS are superior to SFS in terms of the simplified work processes and the reduced number and associated risk of SVs. Eight SVs were found in the PFS system versus 21 in the SFS system. An SV example with high risk in the SFS system was a medication might need to be "drawn-up during surgery while completing other requests simultaneously." This SV added cognitive complexity during anesthesiology medication delivery. However, it did not exist in the PFS system. Conclusions: The inclusion of PFS into anesthesiology medication delivery has the potential to improve system safety and work efficiency. However, there were still opportunities for further improvement by addressing the remaining SVs and newly introduced complexity. Abstract : In a work system analysis using human factors principles conducted in the operating rooms and pharmacy of a single large academic medical center, prefilled syringe were associated with simpler use and fewer system vulnerabilities compared with self-filled syringe. Use of prefilled syringe might improve the safety of perioperative medication delivery if these findings are confirmed in larger multicenter studies.